Advanced Simulation of Metal Additive Manufacturing Using Maraging Steel and Nickel Alloy - Hanzl, Pavel; Zetková, Ivana; Daňa, Milan; Nozar, Martin (Manufacturing Technology Journal, 2020)
Direct Metal Laser Sintering (DMLS) is a method which builds metal parts in a layer by layer procedure. The melting of metal powder by a laser beam is a complex physical metallurgical process and successful processing of the whole manufacturing procedure requires complex management. Therefore, a successful result is not guaran-teed. The print job is designed based on the designer?s personal experience, and the possibility to verify the cor-rectness of a job proposal would save time and money. Nowadays, there are many kinds of software which allow timely detection of errors in the print job design. This paper deals with demonstrations of print task simulations. The results from actual simulations are useful as support for the print job designer, but they do not completely substitute for real production tests of parts.
Keywords: Simulation; Direct Melting Laser Sintering; Metal Additive Manufacturing